Insights from clinical research completed during the west Africa Ebola virus disease epidemic. Issue 9 (September 2017) - Rojek, Amanda; Horby, Peter; Dunning, Jake
Summary: The west Africa Ebola virus disease (EVD) epidemic was extraordinary in scale. Now that the epidemic has ended, it is a relevant time to examine published studies with direct relevance to clinical care and, more broadly, to examine the implications of the clinical research response mounted. Clinically relevant research includes literature detailing risk factors for and clinical manifestations of EVD, laboratory and other investigation findings in patients, experimental vaccine and therapeutic clinical trials, and analyses of survivor syndrome. In this Review, we discuss new insights from patient-oriented research completed during the west Africa epidemic, identify ongoing knowledge gaps, and suggest priorities for future research.